Integration of fuzzy Shannon's entropy with fuzzy TOPSIS for industrial robotic system section - Ahmad Jafarnejad Chaghooshi; Mohammad Reza Fathi; Mojtaba Kashef (Journal of Industrial Engineering and Management (JIEM), 2012)
Purpose: The aim of this study is applying a new method for Industrial robotic system selection. Design/methodology/approach: In this paper, the weights of each criterion are calculated using fuzzy Shannon's Entropy. After that, fuzzy TOPSIS is utilized to rank the alternatives. Then we select the best Industrial Robotic System based on these results. Findings and Originality/value: The outcome of this research is ranking and selecting industrial robotic systems with the help of Fuzzy Shannon's Entropy and Fuzzy TOPSIS techniques. Originality/value: This paper offers a new integrated method for industrial robotic system selection.
Keywords: 650; entropy; TOPSIS; fuzzy set; robotic systems